Pelatihan dan Pengenalan Open Journal System (OJS) untuk Publikasi Ilmiah - Hadi Sirad, Mochammad Apriyadi (Patria Artha Journal of Community (PKM), 2023)
Open Journal System (OJS) is a web-based online journal management developed by PKP. OJS facilitates the management of online journal publishing ranging from the receipt of manuscripts from authors, distribution of manuscripts, examination of manuscripts, editing manuscripts to publishing journals. Articles that have been created will be sent through the Open Journal System (OJS). Open Jurnal System is open source software used to manage online scientific journals. Open Jurnal System (OJS) is a journal management application whose publication system is web-based developed by PKP. Based on this background, the practitioner wants to do the service in order to equip students in terms of writing articles to be published in accredited national journals and send through the open journal system. This training is carried out for the introduction of journals to students as a means of publication of their work if graduation requirements are imposed at the Faculty of Engineering, Khairun University. One of the main problems is related to the unavailability of facilities for students to publish their work or research on campus. The training for the introduction of the Open Journal System was carried out using the PROtek website of the Scientific Journal of Electrical Engineering owned by the Electrical Engineering Study Program of the Faculty of Engineering, Khairun University. Based on the results of the service, it can be concluded that final-level students can already write research articles in accordance with the standard of articles in accredited national journals, final-level students can already subsubmite articles in OJS 2-based journals. Keywords: Open Journal System (OJS), Artikel, Sinta, PROtek Scientific Journal of Electrical Engineering